KAJIAN SOSIODIALEKTOLOGI BAHASA MASYARAKAT HADRAMIY (STUDI KASUS MASYARAKAT INDONESIA KETURUNAN ARAB DI PASAR KLIWON SURAKARTA) - Hanifah Nida’uljanah, Muhammad Ridwan (Arabic Literature Department, 2017)
This research examines the genetic relationship and separating time of language used by generation of Arab in Pasar Kliwon Surakarta along Arabic language. The data source of this research is Hadramy community in Arabic Department Universitas Sebelas Maret and group of pupils of Hadramy generation studying in SMA Islam Diponegoro Surakarta. The collecting data was done by talking technique and calling up the questions, and continued by noting and recording data. The analyzing data used phonetic equalizing method. The results of the research reveal, first, Pasar Kliwon’n language has historic relationship to Arabic language. The research finds 136 couple words that have genetic relationship among 200 Swadesh used vocabularies, or 68% among them. It clear to be concluded that relationship occurred between two variants of that language. Second, the separating time of language was predicted taking place in 1011 to 1207 (counted from 2017).